Sektor Unggulan Dan Pertumbuhan Ekonomi: Studi Kasus Kota Padangsidimpuan - Khairul Kamal (ITB AAS INDONESIA Surakarta, 2023)
Leading sectors are expected to be able to overcome economic development problems with economic growth rates. The aim of this research is to find out what sectors are the leading sectors in Padangsidimpuan City and to find out how the growth of these leading sectors influences the level of economic growth in Padangsidimpuan City. The type of data used in this research is secondary data obtained from the Padangsidimpuan City Central Statistics Agency and the North Sumatra Province Central Statistics Agency. The results of this research are based on Location Quotient (LQ) analysis, Dynamic Location Quotient (DLQ) analysis, Growth Ratio Model (MRP), and Shift Share analysis, there are four sectors which are the leading sectors in Padangsidimpuan City, namely the electricity and gas procurement sector; wholesale and retail trade sector, car and motorbike repair; transportation and warehousing sector; as well as the accommodation and food and drink provision sector. Based on the results of simultaneous multiple linear regression analysis, leading sectors have a significant influence on the level of economic growth in Padangsidimpuan City. Partially, the electricity and gas procurement sector has a positive and insignificant effect on the level of economic growth. Partially, the wholesale and retail trade sectors; car and motorbike repairs have a positive and insignificant effect on the level of economic growth. Partially, the transportation and warehousing sectors have a positive and significant effect on economic growth. Partially, the accommodation and food and drink provision sector has a negative and insignificant effect on economic growth. Keywords: GDP, leading Sectors, Economic Growth